Indirect Effects Faktor Peran pada Implementasi Patient Center Care terhadap Pelaksanaan Patient Safety - Olivia Talahatu; Muhammad Hadi; Suhendar Sulaiman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to identify factors that play a role in PCC implementation on indicators of hospital service quality (patient safety) based on moderate work motivation. Research method This research uses an analytical observational design with a cross-sectional approach. The results of this study accepted three hypotheses, including the relationship between PCC implementation and patient safety and two indirect effects, namely the role of PCC implementation on patient safety through work motivation and one of the factors of PCC implementation (Measurement of systems and responses) to patient safety. In conclusion, work motivation related to the form of appreciation or reward is the indicator with the most significant value that has a positive effect on the implementation of patient safety if it is supported by the support of factors that play a role in the performance of PCC in the Bhayangkara General Hospital TK IR Said Sukanto, East Jakarta as one of the hospitals. military Keywords: PCC Implementation, Work Motivation, Patient Safety